Iconology revisited: Ambiguity, hybridity, and the limits of Panofsky's methodology - Kaya, Adam Raul (Culture and History: Student Research Papers, 2025)
This article re-examines Erwin Panofsky’s iconology through two case studies: a Gandhāran toilet tray (1st–2nd c. CE) and the grave stele of Eupheros (c. 430 BCE). Panofsky’s tripartite ladder retains pedagogical clarity but presumes stable meanings and shared symbolic codes. The Gandhāran tray’s hybrid motifs resist unitary synthesis, while the Eupheros stele’s apparent coherence dissolves once reception and performativity are foregrounded. Both cases show that cultural stability is produced, not given. The article proposes an iconology-plus: a framework that keeps Panofsky’s steps but embeds them within approaches attentive to hybridity, biography, and image agency.